2011
DOI: 10.1007/s00374-011-0616-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term exposure to enriched CO2 on the nutrient-supplying capacity of a grassland soil

Abstract: Altered soil nutrient cycling under future climate scenarios may affect pasture production and fertilizer management. We conducted a controlled-environment study to test the hypothesis that long-term exposure of pasture to enriched carbon dioxide (CO 2 ) would lower soil nutrient availability. Perennial ryegrass was grown for 9 weeks under ambient and enriched (ambient+120 ppm) CO 2 concentrations in soil collected from an 11.5-year free air CO 2 enrichment experiment in a grazed pasture in New Zealand. Nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Extensive reportsare available in the literature on the mechanisms that underpins this process (Aranjuelo et al, 2014). The increase in growth from elevated CO2 is likely to require more phosphorus, which is taken up from the available phosphorus pool in soil (Gentile et al, 2012;Jin et al, 2013). Several studies have reported that both the magnitude and the direction of the growth response of plants to elevated CO2 depend on P availability (BassiriRad et al, 1997;Jin et al, 2013).…”
Section: Cultural Operationsmentioning
confidence: 99%
“…Extensive reportsare available in the literature on the mechanisms that underpins this process (Aranjuelo et al, 2014). The increase in growth from elevated CO2 is likely to require more phosphorus, which is taken up from the available phosphorus pool in soil (Gentile et al, 2012;Jin et al, 2013). Several studies have reported that both the magnitude and the direction of the growth response of plants to elevated CO2 depend on P availability (BassiriRad et al, 1997;Jin et al, 2013).…”
Section: Cultural Operationsmentioning
confidence: 99%
“…Therefore, based on the leaf P concentrations, we can conclude that the P availability was in the range where nutrient limitation might occur. In a fertilizer experiment using soil from this FACE experi-ment in a controlled environment, Gentile et al (2012) found no difference in leaf P concentrations for aCO 2 and eCO 2 in Lolium perenne (ryegrass) plants but found a P limitation to growth under eCO 2 implying a higher demand for P in this treatment. To put our P status in some context, relationships drawn from fertilizer trials in New Zealand with ryegrass/white clover swards indicate a clover P concentration of 0.26 % is required to gain 90 % of the maximum response to P (Sinclair et al, 1997).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, based on the leaf P concentrations, we can conclude that the P availability was in the range where nutrient limitation might occur. In a fertilizer experiment using soil from this FACE experiment in a controlled environment, Gentile et al (2012) found no difference in leaf P concentrations for aCO 2 and eCO 2 in Lolium perenne (ryegrass) plants but found a P limitation to growth under eCO 2 implying a higher demand for P in this treatment. To put our P status in some context, relationships drawn from fertilizer trials in New Zealand with ryegrass/white clover swards indicate a clover P concentration of 0.26 % is required to gain 90 % of the maximum response 8278 T. Watanabe et al: Reduced N fixation of clover under elevated CO 2 to P (Sinclair et al, 1997).…”
Section: Biogeosciencesmentioning
confidence: 66%